The investigation of the effects of two different polymers and three catalysts on pyrolysis of hazelnut shell - Aydinli, Bahattin; Caglar, Atila (Elsevier BV, 2012)
Abstract This study covers an investigation of three catalyst candidates namely; calcium carbonate (CaCO3), Perlite and potassium dichromate (K2Cr2O7) on pyrolysis of mixtures of hazelnut shell (HS) with ultra-high molecular weight polyethylene (UHMWPE) and polyethylene oxide (PEO) by measuring percentages of solid, liquid and gas products amounts gravimetrically. Pyrolysis processes were executed in a batch type tubular reactor at 500 and 650 °C for fifteen minutes. Catalysts have behaved differently on compounded mixtures. Especially the obtained liquid products from pyrolysis of mixtures shows smooth distribution compared to anomalous results of pure raw materials. The effect of catalysts on the pyrolysis of HS becomes more obvious in the presence of polymers which produces more gaseous product for K2Cr2O7 case. The other catalysts (CaCO3, Perlite) are more effective without addition of polymers which produce more liquid products. The ratio of HS should not be beyond the 0.5 for production of commercial materials and in their possible recycling process such as pyrolysis for acquisition of combustible liquids. These results may allow some clues for compounding of environmentally safe commercial materials, and easy and efficient recycling technologies.
Keywords: 12. Responsible consumption